Predicting sport performance satisfaction in tennis players: The effect of situational variables - F. J. Santos‐Rosa; T. García; R. Jiménez; M. Moya; E. M. Cervelló (Asociación Española de Ciencias del Deporte, 2010)
This study has analyzed the relationships between dispositional and situational variables in competition and the sport performance satisfaction of 151 tennis players. The perception of situational flow, competition task and ego-involvement, and directionality of somatic, cognitive and self-confidence perceptions of anxiety were measured. Results show that satisfaction with sport performance in competition was positively predicted by the situational flow and by task and ego-involvement. The implications of these findings for the process of training and competition are discussed in the document.  Key words: Motivation, pre-competitive anxiety, situational flow, goal involvement, tennis.